Pengaruh Karakteristik Komite Audit Terhadap Manajemen Laba - Merlyn Huang; Eny Purwaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines how audit committee traits impact earnings management. Purposive sampling was used to choose consumer products manufacturing businesses listed on the Indonesia Stock Exchange from 2019 to 2023. This research sampled 55 financial report data from 11 firms. This research employs linear regression tests to examine how audit committee size, independence, frequency of meetings, membership, and gender affect earnings management. Results reveal that audit committee expertise negatively impacts earnings management, demonstrating that experience and competence may improve oversight. The size, independence, number of meetings, and gender of the audit committee all improve profits management. These elements do not ensure ongoing monitoring. This demonstrates that the audit committee's efficacy relies on both its formal tasks and how similarities are used to improve financial reporting openness and quality.